What does the literature say about using robots on children with disabilities? - Cruz, Antonio Miguel; Rios Rincon, Adriana María; Rodriguez Dueñas, William Ricardo; Quiroga Torres, Daniel Alejandro; Bohórquez Heredia, Andrés Felipe (Taylor and Francis Ltd., 2017)
The purpose of this study is to examine the extent and type of robots used for the rehabilitation and education of children and young people with CP and ASD and the associated outcomes.

El propósito de este estudio es examinar la extensión y el tipo de robots utilizados para la rehabilitación y educación de niños y jóvenes con parálisis cerebral y TEA y los resultados asociados.
Keywords: Parálisis cerebral- Daño cerebral; Robótica; Rehabilitación; Autistic spectrum disorder; Cerebral palsy; Robots; Systematic review; Children; Assistive technology; Trastorno del espectro autista; Parálisis cerebral; Robots; Revisión sistemática; Niños; Tecnología de asistencia